Ketersediaan Ruang Terbuka Hijau Berbasis Pelestarian Lingkungan di Kabupaten Sidoarjo - Rizky Novita (Universitas Islam Darul Ulum Lamongan, 2018)
Ideal Development (Green Room Availability Study Kabupaten Sidoarjo). Development is absolutely necessary in advancing a limited land area but an obstacle to creating a balanced development with nature so that the arrangement of space is needed in order to create the ideal development. Descriptive qualitative research results indicate that the rule requiring the arrangement of green spaces provide a minimum of 30% of the area of green space Overall however, Kabupaten Sidoarjo only able to meet the quota of 21.6% of the area of 177.147 km2 of green space that has been targeted on a total area of 591.59 km2 , To that end, the macro planning (revitalization function green space) and a micro plan (the greening of public facilities) have made the local government in an effort to meet and maintain the availability of green space. The fulfillment of these green spaces also requires awareness throughout society Kabupaten Sidoarjo in treating green space as a development asset.